FILANTROPI ISLAM RUMAH SABILILLAH DAN PENANAMAN KARAKTER KEPEDULIAN SOSIAL PADA SISWA DI SDIT AN NAJAH JATINOM KLATEN - Zaid Munawar (Elementary: Jurnal Ilmiah Pendidikan Dasar, 2018)
The purposes of this research were (1) to describe the implementation of social ewareness character to students in SDIT An Najah Jatinom Klaten, (2) to describe the change in character building of social ewareness from students in SDIT An Najah Jatinom Klaten. This research was a qualitative research. Methods of data collection were conducted in four ways, namely (1) Observation, (2) Interview, (3) Documentation, (4) Questionnaire containing student social attitude at SDIT An Najah. The results of this research are: (1) the implementation of social character building of students in SDIT An Najah is done through socialization strategy, fundraising strategy and distribution strategy in Islamic philanthropy of Rumah Sabilillah, and (2) Islamic Filantrophy approach of Rumah Sabilillah able to improve character social awareness of students in SDIT A Najah, as evidenced by several things namely; the increasing of philanthropy fund of Rumah Sabilillah, the increasing of the mustahiq that can be supported, and the widespread use of philanthropy fund which is not only limited to the five excellent programs of Rumah Sabilillah, but also able to provide assistance to the construction of mosque in Jatinom subdistrict and surrounding area.